Réflexions sur l’appropriation du théâtre historique élisabéthain par la scène britannique contemporaine : usages de Macbeth dans Thirteenth Night de Howard Brenton (1981) et Dunsinane de David Greig (2010) - Line Cottegnies (Sillages Critiques)
This article deals with how Shakespeare can be used as a matrix, either accommodating or problematic, to shape past or present events into a historical perspective on the contemporary stage, and looks at two plays that are explicit adaptations of Macbeth, Howard Breton’s Thirteenth Night (1981) and David Greig’s Dunsinane (2010). These two plays can help us think in a contrastive way about the question of adaptation. They show a complex rapport with the canonical source. Both plays are based on a very different aesthetics, yet they share a similar narrative logic, as well as the influence of the Jacobean aesthetics of cruelty. The echoes of Macbeth suggest an ambivalent perspective on history, between the hope that it might be possible to learn from the past to despair at the endless return of the same, as conflicts seem to only lead to a short-lived resolution. Of the two adaptations it is Greig’s that manifests the most dialogical relationship to the Shakespearean source: by offering an alternative sequel to the play which puts the Scottish fight for independence centre-stage, Greig offers a critical reading of Macbeth, implicitly that the question of English imperialism is a blind spot in Shakespeare’s play.